2011
DOI: 10.1063/1.3615287
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of point-defect diffusion in a two-dimensional colloidal crystal

Abstract: Influence of crystal orientation and ion bombardment on the nitrogen diffusivity in single-crystalline austenitic stainless steel J. Appl. Phys. 110, 074907 (2011) Vacancy properties in germanium probed by cobalt diffusion J. Appl. Phys. 110, 033526 (2011) Measurement of photostimulated self-diffusion in silicon J. Appl. Phys. 109, 103708 (2011) Physical modeling and implementation scheme of native defect diffusion and interdiffusion in SiGe heterostructures for atomistic process simulation J. Appl. Phys. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…These colloidal model systems allow manipulation of the kinetic states of individual particles by means of optical tweezers, for example to create vacancies and interstitials [14,15,16,17,18], or to manipulate many-particle defect reactions [19]. However, the response of colloidal crystals to large thermal and external excitations of a single particle within the lattice is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These colloidal model systems allow manipulation of the kinetic states of individual particles by means of optical tweezers, for example to create vacancies and interstitials [14,15,16,17,18], or to manipulate many-particle defect reactions [19]. However, the response of colloidal crystals to large thermal and external excitations of a single particle within the lattice is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…6,23 Note that both vacancies and interstitials are known to have many distinct topological configurations with different symmetries. 6,23 Note that both vacancies and interstitials are known to have many distinct topological configurations with different symmetries.…”
Section: B Microscopic Mechanisms For Diffusion In Crystal and Hexatmentioning
confidence: 99%
“…The examination of the energetics of vacancies in L-J crystals suggested that a sufficiently deep valley in the curve of the interaction potential is essential to support intact vacancies [21,22]. In contrast, the integrity of vacancies was hardly observed in systems of purely repulsive particles where the n-point vacancies tend to collapse into various defect clusters [15,28,[33][34][35]. We therefore expect a distinct scenario of vacancy dynamics in L-J crystals.…”
Section: Introductionmentioning
confidence: 97%
“…The problem of how the vacancy dynamics depends on vacancy size and temperature is still unclear. In addition, it appears that the behavior of vacancies is very sensitive to the nature of the interaction potential through a survey of the energetics [21][22][23][24] and dynamics [25][26][27][28][29] of vacancies in two-dimensional crystals with the Yukawa potential [25,[27][28][29], Gaussian core [30], the repulsive 1/r 3 potential [23], the purely repulsive Weeks-Chandler-Andersen potential [20], and the Lennard-Jones potential [21,22]. The generic, formally simple Lennard-Jones (L-J) potential represents an important form of interaction that has been extensively used to model a large variety of chemical and physical bonds [31].…”
Section: Introductionmentioning
confidence: 99%